Pulmonary invasive mucinous adenocarcinoma - Chang, Wei‐Chin; Zhang, Yu Zhi; Nicholson, Andrew G (Histopathology, 2024)
Invasive mucinous adenocarcinoma (IMA) is a relatively rare subtype of lung adenocarcinoma, composed of goblet and/or columnar tumour cells containing abundant intracytoplasmic mucin vacuoles. While a majority of IMAs are driven by KRAS mutations, recent studies have identified distinct genomic alterations, such as NRG1 and ERBB2 fusions. IMAs also more frequently present as a pneumonic‐like pattern with multifocal and multilobar involvement, and comparative genomic profiling predominantly shows a clonal relationship, suggesting intrapulmonary metastases rather than synchronous primary tumours. Accordingly, these unique features require different therapeutic approaches when compared to nonmucinous adenocarcinomas in general. In this article, we review recent updates on the histopathological, clinical, and molecular features of IMAs, and also highlight some unresolved issues for future studies. Classical and variant morphology of invasive mucinous adenocarcinoma.